HEMATOLOGICAL MALIGNANCIES. LYMPHOCYTIC LEUKAEMIA - Peter F. Litvitsky; Tatyana N. Zhevak ("Paediatrician" Publishers LLC, 2016)
The lecture gives characteristics of leukaemia: tumours of hematopoietic cells, its types, etiology and pathogenesis key links, clinical manifestations and mechanisms of its development, caused systemic disorders, principles of its diagnosis and treatment.